Catheter-Directed Thrombolysis of Arterial Thrombosis - Wicky, Stephan; Pinto, Erique Guedes; Oklu, Rahmi (Seminars in Thrombosis and Hemostasis, 2013)
Thrombotic or embolic arterial occlusive disease can lead to profound ischemia and, without emergent revascularization, is associated with significant morbidity and mortality. Significant advances in the management of arterial occlusive disease range from newer thrombolytic agents to innovative catheter designs to enhance thrombolysis and thrombectomy. Most of these advances have been directed toward the management of acute limb ischemia; therefore, we review the management of limb ischemia with emphasis on endovascular interventions.
Keywords: thrombosis; catheter-directed thrombolysis; artery